TRANSCRANIAL DIRECT CURRENT STIMULATION AND AUGMENTATIVE AND ALTERNATIVE COMMUNICATION FOR CHILDREN WITH CEREBRAL PALSY: A RANDOMIZED, DOUBLE-BLIND, CONTROLLED CLINICAL TRIAL (CIPEEX, 2025)
The objective of this research project is to compare the effects of ten speech therapy sessions using Augmentative and Alternative Communication (AAC) during transcranial direct current stimulation (tDCS) on the active dorsolateral prefrontal cortex and placebo in the Activity and Participation domain of the ICF of children with CP. This is a randomized, placebo-controlled, double-blind clinical trial involving 24 children diagnosed with CP, aged between 6 and 12 years. Participants will be assessed one week before, one week after, and one month after the end of the intervention, using the Communication Matrix, Pediatric Evaluation of Dysfunction Inventory, and the Participation and Environment Measure – Children and Youth. The experimental group will undergo speech therapy with AAC associated with the application of active anodal tDCS on the left dorsolateral prefrontal cortex. The control group will undergo speech therapy with AAC associated with placebo tDCS. The intervention will consist of ten sessions, conducted over two consecutive weeks, each lasting 20 minutes. Considering the potential effect of anodal tDCS on the left dorsolateral prefrontal cortex, it is expected that the intervention will increase the effect size of speech therapy with AAC in children with CP.
Keywords: cerebral palsy; child; communication; language; speech therapy; transcranial direct current stimulation